EFFECT OF HEAT PROCESSING ON CAROTENE AND ASCORBIC ACID CONTENT OF CARROT-FRUIT JUICE BLENDED NECTAR - T. V. YADAV (The Bioscan, 2015)
The experiment comprised of nine different treatment combinations of nectar made from juice blends with carrot juice as base juice, blended with aonla, pomegranate and grape juice at the ratio of 85:15 each and exposed to pasteurisation temperatures of 80º, 85º and 90ºC for 5, 2 ½ and ½ minutes, respectively. They were then stored at ambient conditions (20±40C) for 90 days and tested for nutritional, physico-chemical and sensory evaluation.It was observed that among all the treatments, at the end of 90 days the nectar made from carrot-aonla (85:15) juice blend, processed at 90ºC for ½ minute, proved to be better in respect of all the quality parameters viz., ascorbic acid (12.61 mg/100mL), â carotene (0.48 mg/100mL) and organoleptic score (6.91), pH (5.76), acidity (0.231%), TSS (15.27), Total Sugar (12.11%), Reducing Sugar (4.89%) and also B: C ratio (3.69: 1) of carrot-aonla (85:15) juice blends. The results showed that processing treatment at 90ºC for ½ minute was most effective and possessed better values for all the quality parameters.